The Value of Preventing Malaria in Tembien, Ethiopia - Whittington, Dale (The World Bank, 2000)
January 2000 - Despite the great benefits from preventing malaria, the fact that vaccine demand is price inelastic suggests that it will be difficult to achieve significant market penetration unless the vaccine is subsidized. The results are similar for bed nets treated with insecticide. Cropper, Haile, Lampietti, Poulos, and Whittington measure the monetary value households place on preventing malaria in Tembien, Tigray Region, Ethiopia. They estimate a household demand function for a hypothetical malaria vaccine and compute the value of preventing malaria as the household's maximum willingness to pay to provide vaccines for all family members. They contrast willingness to pay with the traditional costs of illness (medical costs and time lost because of malaria). Their results indicate that the value of preventing malaria with vaccines is about US